Excellent Service dalam Peningkatan Kualitas Pelayanan Administrasi Dinas Kependudukan dan Pencatatan Sipil Kota Malang - Khoiru annisa, Khofifah; Prathama, Ananta (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Population administrative services should be efficient, productive, responsive, and accountable. In this case, public satisfaction should be a top priority. The type of research used is qualitative descriptive research. The aim of this study is to understand the concept of excellent service used to improve the quality of administrative services provided by the Department of Population and Civil Registration of Poor Cities. Primary and secondary data are used, and data collection techniques are done with interviews, documentation, and observations. Data analysis includes collective, reduction, presentation, and conclusion. The concept of Attitude, Attention, and Action (3A) Primary Service is used by the Poor City Civil Registration and Occupation Service. For the attitude points, which have demonstrated behavior and attitude that are purposeful and conscious, and the attention points, which have shown full concern to the applicant in terms of meeting the applicant's needs and giving criticism and advice, For the final action points, I have been responsible for performing tasks according to the service officer's job desk and doing so on the job. Thus, the quality of administrative services in the Department of Occupation and Civil Registration of Poor Cities can be improved and the status of primary service retained in accordance with the concept of excellent service